General dentists' perceptions and clinical management of hypomineralised second primary molars (HSPM) in Ireland - Oleg?rio da Costa, Isabel; O'Connell, Anne (My University, 2023)
Purpose: This questionnaire aimed to explore how general dentists in the Republic of Ireland perceive and manage hypomineralised second primary molars (HSPM). Methods: Following ethical approval, a validated structured questionnaire containing 19 questions was sent to Irish dentists using Survey Monkey. Questions on awareness, dentist’s experience, barriers to care and clinical scenarios with different treatment options were included. Binary outcomes and independent variables were compared using logistic regression analysis (α = 5%). Results: Responses from 279 general dentists were analysed. The majority of dentists were aware of HSPM (72%) and most dentists felt confident in diagnosing HSPM (71%). Dentists who had practiced for ≥ 15 years were significantly more likely to document HSPM frequently compared to those with less experience (OR 0.29; p = 0.012). No significant association was found between confidence in HSPM diagnosis and other variables, such as age group, years of practice and workplace. Dentists not working in private practice reported to be less comfortable in the management of HSPM (OR 0.49; p = 0.030). The most cited barrier to management of HSPM was child’s behaviour. A broad variation was observed in the clinical scenarios, in particular when treatment planning more severe HSPM. Conclusions: In general, Irish dentists are aware of HSPM and are confident in diagnosis and management. Variation existed in treatment options reflecting the disparity that exists in clinical management.
PUBLISHED
Keywords: Treatment; Management; Awareness; Hypomineralised second primary molars